The role of school supervisors in planning mentoring for vocational school principals in North Bengkulu, Indonesia - Lukisworo Eko Dewandari; Manap Somantri; Muhammad Kristiawan; Ari Andre Rianyansa (Universitas Muhammadiyah Malang, 2026)
Background- Many school supervisors still rely on conventional, top-down supervision practices, resulting in mentoring plans that are insufficiently reflective, data-driven, and aligned with the actual needs of school principals. Objectives-This study aims to describe the role of school supervisors in planning assistance for vocational school principals in North Bengkulu Regency. The focus of the research is directed at how supervisors develop plans for each mentoring cycle, including the initial stage, mentoring of education unit programs, program implementation, and reporting and follow-up. Method-This study uses a qualitative descriptive approach with three vocational school supervisors as the main respondents and three principals as triangulation sources. Data were collected through in-depth interviews and documentation, analyzed using Miles and Huberman's interactive model. Results- The results show that mentoring planning was carried out systematically through reflective, needs-based, and collaborative processes, including mapping change commitments, developing differentiated strategies, designing coaching and mentoring scenarios, and preparing reflective reports. These findings indicate a shift in supervision from a control function to a collaborative mentoring approach that strengthens principal leadership. Conclusion-This study concludes that systematic, reflective, and collaborative mentoring planning improves the quality of supervision and supports more effective principal leadership. Its novelty lies in the context of vocational schools in North Bengkulu, which offers an adaptive model for other regions and enriches the literature on mentoring across the full supervisory cycle.